PENTINGNYA PENGUASAAN LITERASI TEKNOLOGI INFORMASI DAN KOMUNIKASI BAGI GURU MADRASAH IBTIDAIYAH DALAM MENYIAPKAN SISWA MENGHADAPI REVOLUSI INDUSTRY 4.0 - Munawir Gazali; Made Ayu Pransisca (LPPM Institut Pendidikan Nusantara Global, 2021)
In the era of the industrial revolution 4.0, it is a tough challenge for all Indonesian teachers. The quality of education is a measure of Indonesia's success in facing the era of the industrial revolution 4.0. A teacher at this time is required to be technologically literate because the quality of a teacher who is empty of technology will not be able to instill a